Penguatan Keislaman Dalam Pembentukan Karakter - Lathifatul Izzah (LITERASI (Jurnal Ilmu Pendidikan), 2015)
Abstract Islam is religion of peace, mercy religion, religious bearer of glad tidings that provide shade and compassion in the universe. His people should practice as exemplified by the teachings of the apostles, especially the prophet Muhammad. The people who claim Islam, but in life and movement resulted in misery, doom, and destruction for humans and other creatures, certainly it is not the Muslims. He only utilizes Islam and destroys Islam. Islam has a fairly simple doctrine that includes faith, Islam and charity, but capable of coloring the entire activity and life of the people. Islam can determine the human character, both lauwwama, amarah, and mutmai’nnah not necessarily Islamic deliver and pick, but with Allah’s approval man himself working on an ongoing basis, gradual and consistent. Keywords: Strengthening Islamic, character formation